Implementation of the Talaqqi Method in Quran Memorization Learning and Its Relevance to Spiritual Intelligence at the As-Sunnah Islamic Boarding School in West Nusa Tenggara - Eka Sastra Wijaya; M. Jadid Khadavi; Benny Prasetiya (Immortalis Journal of Interdisciplinary Studies, 2026)
This research is motivated by the importance of implementing the talaqqi method as a traditional yet relevant approach in learning to memorize the Qur'an in Islamic boarding schools, especially in the context of the increasing need for education that emphasizes not only cognitive aspects but also spiritual strengthening. This study aims to analyze the implementation of the talaqqi method in the process of memorizing the Qur'an and examine its relevance to the formation of spiritual intelligence of students at the Assunnah NTB Islamic Boarding School. The research method used is a qualitative study with a descriptive approach, data collection methods through observation techniques, in-depth interviews, and documentation to obtain comprehensive data related to the implementation of talaqqi. The results of the study show that the talaqqi method is implemented through the stages of talqin, tashih, kitabah, and tasmi' hafalan which are carried out systematically and intensively, so that it can improve the accuracy of memorization, discipline, and the quality of the students' relationship with the Qur'an. The findings also revealed that the ongoing direct interaction between the ustadz and the students during the talaqqi process significantly contributes to strengthening spiritual intelligence, as reflected in increased religious awareness, deepened appreciation of worship, and internalization of moral values. This research confirms that the talaqqi method is not only effective from a pedagogical perspective but also has important implications for shaping the students' spiritual character.